PENGEMBANGAN ADOBE FLASH BERBASIS ANDROID UNTUK MENINGKATKAN KEMAMPUAN RESPRESENTASI DAN DISPOSISI MATEMATIS SISWA SMK - Delisbeth Delisbeth; Dede Suratman; Bistari Bistari (Universitas Tanjungpura, 2019)
AbstractThis study aims to reveal about the development of Android-based Adobe Flash learning media to improve the representation and disposition capabilities of three dimensional geometry that are reviewed from the Early Mathematical Knowledge of 2nd Usaha Perjalanan Wisata (UPW) class XII of Vocational School Number 1 at Tanjungpinang, Riau Islands Province. This research using ADDIE model. The subject research was one class with 31 student. From the results of the study the following conclusions are obtained: (1) The process of developing Android-based Adobe Flash learning media through several stages, (2) The ability of students' mathematical representation to increase very significantly after using Adobe Flash Android-based learning media of mathematics from an average pretest of 59.77% and the average posttest results of 85%, (3) Disposition mathematical students increases after using Adobe Flash math learning media based on Android. This was concluded from data on disposition survey which included: self-confidence, flexible thinking, perseverance, interest and curiosity and monitoring and evaluation. Keywords: The ability of mathematical representation, mathematical disposition ability, ADDIE Development Model.